2011
DOI: 10.1002/jso.21865
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lymphatic drainage patterns and implications for the extent of neck dissection in head and neck melanoma patients

Abstract: Almost a quarter of head and neck melanomas metastasize outside clinically predicted neck levels. Neck surgery guidelines of The Netherlands Cancer Institute provide for a smaller number of discordant sentinel nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 22 publications
5
35
0
4
Order By: Relevance
“…Therapeutic lymphadenectomy is the preferred treatment in patients with regional clinical lymph node involvement from melanoma (27). The 10-year survival rate in patients with metastatic involvement of regional lymph nodes is approximately 20-40% (28).…”
Section: Therapeutic Lymphadenectomymentioning
confidence: 99%
“…Therapeutic lymphadenectomy is the preferred treatment in patients with regional clinical lymph node involvement from melanoma (27). The 10-year survival rate in patients with metastatic involvement of regional lymph nodes is approximately 20-40% (28).…”
Section: Therapeutic Lymphadenectomymentioning
confidence: 99%
“…Also, selective SLND using lymphoscintigraphy allows the identification of affected lymph nodes that would not be routinely evaluated during an elective nodal dissection such as in-transit lymph nodes and lymph nodes in minor nodal basins (e.g., popliteal and epitrochlear regions) [Sumner et al, 2002]. Lymphoscintigraphy is also essential for selective SLND in head and neck melanomas as these have complex and less predictable lymphatic drainage patterns, resulting in lower SLN identification rates and higher FN rates (Klop et al, 2011;Leong et al, 1999). For these reasons, cutaneous lymphoscintigraphy has become a routine component of the management of most melanoma patients.…”
Section: The Sentinel Lymph Node In Melanomamentioning
confidence: 99%
“…Recurrence and death in SLN negative patients may be related to FN SLN results or a pure hematogenous spread (Leong et al, 2004. In particular, head and neck melanomas have a higher FN rate, over 12% in some studies (Klop et al, 2011); this is likely due to a complex lymphatic drainage pattern with multiple basins in the head and neck (Leong, 2011). FN results for selective SLND may result from failed preoperative lymphoscintigraphy, including injection techniques and interpretation of the lymphoscintigraphy, failed intraoperative lymphatic mapping, failed pathologic identification of microscopic disease, and "skip" metastasis (Leong, 2004).…”
Section: Negative Nodementioning
confidence: 99%
“…Detailed mapping of head and neck lymphatics has shown unexpected drainage patterns in 8-43% of patients. [Klop et al, 2011;O'Brien et al, 1995]. A study by Kelly et al showed that, while the procedure was safe, there was a false negative rate of 9.5% and a failure to locate a lymph node in 32.5% of patients [Kelly et al, 2009].…”
Section: Slnb For Head and Neck Melanomasmentioning
confidence: 99%